Salutogenic qualities of midwifery care: A best-fit framework synthesis. Issue 3 (May 2021) - Mathias, Laura A.; Davis, Deborah; Ferguson, Sally
Abstract: Background: Although midwifery care is wellness-based and promotes normal physiology, it exists within a medical model that focuses on risk aversion and disease prevention. Salutogenic theory could provide an alternative approach to midwifery care, supporting health-promoting factors, rather than solely avoiding adverse events. Aims: The aim of this study was to explore women's experiences of their midwifery care and identify salutogenic aspects of midwifery care. Methods: Best-fit framework synthesis was used to analyse 349 quotes about women's experiences of midwifery care from 31 qualitative studies in ten high-income countries. Key salutogenic concepts of comprehensibility, manageability and meaningfulness were used as the basis for coding, and thematic analysis was used to expand and clarify the framework to best fit the data. Findings: Definitions for the salutogenic aspects of midwifery care were developed. Comprehensibility (cognitive aspects of health): ways that midwives help women increase predictability and preparation during childbearing through a predictable caregiver, a predic table s ystem and preparation for an unpredictable experience . Manageability (behavioural aspects of health): ways that midwives enhance and support a woman's internal resilience, adding extra support when needed, and strengthen women's external resources through connections to family, community and specialist care. Meaningfulness (emotional/spiritual aspects of health): ways that midwives encourage the commitment and engagement of childbearing women by providing care through a personalised relationship, by cultivating a woman's autonomy . Conclusion: Findings of this study may be used to further research into ways that salutogenic theory can bring a health and wellness-focused agenda to midwifery policy and practice.